Semiotic Analysis of the Lyrics of the Song "Kembali Pulang” by Suara Kayu and Feby Putri - Indriani, Atika Nurwan; Ninggar, Emirullyta Harda (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2024)
This study aims to find out and analyze the meaning of the lyrics of the song "Kembali Pulang" in collaboration between Suara Kayu and Feby Putri. This research uses the Semiotics method developed by Roland Barthes. Semiotics developed by Roland Barthes is the concept of order of meaning. The first sequence, which Barthes calls denotation, describes the relationship between the signifier and the signified in the sign and the relationship between the sign and its reference in external relations is called connotation. The finding in the lyrics of the song "Kembali Pulang" is that the writer of this song wants to convey that in life, humans must observe their surroundings, where there are still people who want to be a place to lean on when in life they get cursed at, people don't care about them, but there are still people who wants to make himself a place to come home to. The lyrics of the song "Kembali Pulang" have a deep meaning, namely someone who is abroad far from family then gets hurt, disappointment, and sadness. The lyrics of this song want to convey that we are never alone, there are always people who are ready to be our home. However, we are less aware of and appreciate its existence. The songwriter wants to convey that the wounds received from the journey can be healed by returning to a place that makes us safe and peaceful to calm down. Convenience is what a person needs in living life, comfort can be obtained from oneself and others.